Health expenditure: how much is spent on health and care worker remuneration? An analysis of 33 low- and middle-income African countries - Hapsatou Toure; Maria Aranguren Garcia; Juana Paola Bustamante Izquierdo; Seydou Coulibaly; Benjamin Nganda; Pascal Zurn (BMC, 2023)
Abstract Objectives To assess the amount spent on health and care workforce (HCW) remuneration in the African countries, its importance as a proportion of country expenditure on health, and government involvement as a funding source. Methods Calculations are based on country-produced disaggregated health accounts data from 33 low- and middle-income African countries, disaggregated wherever possible by income and subregional economic group. Results Per capita expenditure HCW remuneration averaged US$ 38, or 29% of country health expenditure, mainly coming from domestic public sources (three-fifths). Comparable were the contributions from domestic private sources and external aid, measured at around one-fifth each-23% and 17%, respectively. Spending on HCW remuneration was uneven across the 33 countries, spanning from US$ 3 per capita in Burundi to US$ 295 in South Africa. West African countries, particularly members of the West African Economic and Monetary Union (WAEMU), were lower spenders than countries in the Southern African Development Community (SADC), both in terms of the share of country health expenditure and in terms of government efforts/participation. By income group, HCW remuneration accounted for a quarter of country health expenditure in low-income countries, compared to a third in middle-income countries. Furthermore, an average 55% of government health expenditure is spent on HCW remuneration, across all countries. It was not possible to assess the impact of fragile and vulnerable countries, nor could we draw statistics by type of health occupation. Conclusions The results clearly show that the remuneration of the health and care workforce is an important part of government health spending, with half (55%) of government health spending on average devoted to it. Comparing HCW expenditure components allows for identifying stable sources, volatile sources, and their effects on HCW investments over time. Such stocktaking is important, so that countries, WHO, and other relevant agencies can inform necessary policy changes.